PENEMUAN HUKUM OLEH HAKIM TERHADAP KASUS CAROK AKIBAT SENGKETA TANAH DALAM MASYARAKA MADURA - Afif, Muhammad (Kopertis Wilayah X, 2018)
Carok is a violent conflict of Madurese that arises and is caused by a matter of self-esteem. Carok as an institutionalization of Madurese violence, in the form of attempted murder using sharp weapons, is generally clurit. What is done by men against other men who have been considered to have committed harassment against self-esteem. The formulation of the problem of this paper is: 1) what is the occurrence of carok as a judge's consideration in making a decision in court? 2) how is the theory of legal discovery by the judge in imposing criminal decisions on carok custom cases in Surabaya? This research on scientific work, in the form of normative legal research (normative juridical). In normative juridical research, this study focused on reviewing and examining legal findings by judges on carok cases due to land disputes in the Madura community, so that later the writer could elaborate legal findings by judges against carok cases. due to land disputes in Madura society. Carok is an act that is very contrary to the criminal law in Indonesia, because the effect is detrimental to others, it could cause injury, and die. Judges in deciding disputes must have several stages and theories, namely the stage of analyzing a criminal act, the stage of analyzing criminal responsibility, the stage of determining criminal proceedings (the stage of contradicting, the stage of qualifying, the stage of concluding.